Theoretical approaches to the phenomenon of mobbing in modern psychological literatur - Velichko, M. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article reveals the phenomenon of the phenomenon of mobbing as a kind of psychological violence in the group and personality relationships. Theoretical approaches to defining the phenomenon of mobbing and its forms. The main characteristics of mobbing were identified: negative actions by one or more persons towards the victim; systematic behavior in such behavior; a significant difference in the ratio of forces. It has been found that these actions can take many forms, but some guidelines remain. It has been found that harassers (harassers) use the following physical effects: punches, pushes, beats, captures and other types of physical coercion. In this form of violence, there are clear gender differences. Yes, boys are more likely than girls to use means of physical influence. Most often, both boys and girls use verbal influence. The article analyzes the international and domestic experience, as well as the known specific situations, which showed that the problem of mobbing is extremely difficult to overcome, as it gets public only in extreme manifestations, and in other cases is sufficiently hidden, such that is generally not made outside of a social group or collective. This is due to the stereotypical social attitudes about the unwillingness to disclose inside information and to accuse the victim of ill-treatment. Theoretical analysis has shown that the limit of manifestation of aggression of a collective to one of the students is depriving oneself of dignity, mental and physical health, creating negative moments with threat to the life of an individual, since life, health and right to honor are the highest values that are officially protected by the Constitution of Ukraine, the Declaration on the Rights of the Child, the Convention on the Rights of the Child, various laws and codes. It was found that the relevant areas of research for the problem of mobbing are the prevention of its manifestation in different types of groups (labor, child, student, etc.), the search for effective forms of work with victims of harassment, subjects of mobbing, and the formation of a tolerant corporate culture.